The PELATIHAN DAN PENDAMPINGAN PENGGUNAAN CANVA DI DESA GUMBRIH, KECAMATAN PEKUTATAN, KABUPATEN JEMBRANA - Gerson GF Feoh; I Wayan Ruspendi Junaedi; I Gusti Bagus Rai Utama (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
In order to improve business management, ethics in consumer behavior, and improve the quality of product promotion or marketing from Gumbrih Village, Pekutatan District, Jembrana Regency, Dhyana Pura University through the community partnership program Catu Graha Mandiri Gumbrih Village Owned Enterprise (BUMDES) provides training and assistance. one of them is in maximizing the Canva application to improve the quality of promotion and marketing of the products of the BUMDes business of Catu Graha Mandiri, Gumbrih. One of the expected outcomes from partners is an increase in the ability to use appropriate technology for the quantity, quality of product marketing and business of BUMDES Catu Graha Mandiri Gumbrih including business marketing using social media. The impact of intensive training and mentoring is reflected in the data on questionnaires distributed before (pre-test) and after (post-test) this Partnership Program, where there is an increase in knowledge ability in 30 training and mentoring participants from an average score of 60.7 to an average score of 97 so that it can be concluded that the knowledge of the management of BUMDES Catu Graha Mandiri Gumbrih businesses has increased so it is hoped that it will also have an impact on the quantity and quality of businesses including the marketing of these businesses using social media.